Regulation of multinational banks: a theoretical inquiry - Giacomo Calzolari; Gyongyi Loranth (European Central Bank (ECB), 2005)
This paper examines prudential regulation of a multinational bank (MNB hereafter) and shows how regulatory intervention depends on the liability structure and insurance arrangements for non local depositors (i.e. on the representation form for foreign units). Shared liability among the MNB's units gives higher incentives for regulatory intervention than when units are legally separate entities. Cross-border deposit insurance provides lower incentives to intervene than when the regulator only has to compensate local depositors. We study the impact of shared liability and deposit insurance arrangements on regulators' incentives to monitor and acquire information on MNB's activities. Furthermore, by describing regulatory intervention and monitoring we also draw implications on the MNB's preferences over the form representation for foreign units, and discuss the effects of regulators' behavior on both MNB's lobbying and international resources shifting.
Keywords: L51; F23; G21; G28; 330; Branch; multinational banks; Prudential Regulation; Representation Form; Subsidiary; Internationale Bank; Bankenregulierung; Bankenaufsicht; Theorie